Alcohol Consumption Detector for Classroom Using IoT - Dr. V.Vinodhini; Abinayaa. V; Nandhini. J; Vignesh. B (International Journal of Engineering and Management Research, 2023)
The primary goal of the project is to develop a system that can detect the presence of alcohol in a classroom environment using an alcohol sensor and IoT technology. The system will be designed to monitor the classroom environment continuously and alert the teacher and school administration when alcohol is detected. . The system will consist of an alcohol sensor that will be placed in the classroom. This sensor will be able to detect the presence of alcohol vapors in the air. The alcohol sensor will be connected to a micro-controller, which will process the data and send it to the cloud through the internet. In the cloud, the data will be stored and analyzed. An application will be developed to display the results of the alcohol detection. The application will provide real-time information about the alcohol levels in the classroom. It will also display historical data and trends, which can help the school administration to identify patterns and take corrective actions. The system will be designed to send notifications to the teacher and school administration in case of alcohol detection. This will enable them to take appropriate actions, such as contacting parents, counseling students, or taking disciplinary actions. The notifications can be sent through email, text message, or a dedicated app. Overall, the project aims to help prevent alcohol consumption among students in schools. Alcohol consumption can have a significant impact on students' health and academic performance. By detecting alcohol in the classroom environment, the system can provide an early warning system, enabling school administration to take preventative measures and provide support to students who may be at risk.